ICD-11: Organizational and Legal, Medical and Pharmaceutical, Social and Economic Issues of Implementation of the Program of State Guarantees of Medical Care in 2022 in Ukraine, Based on The Fundamental Principles of the European Union - Ivanishyn-Hayduchok, Liubov; Shapovalova, Viktoriia; Shapovalov, Valerii (SSP Modern Pharmacy and Medicine, 2022)
The development of health care and the pharmaceutical industry is based on the principles of the Constitution of Ukraine, the fundamental principles of the European Union, the basics of medical and pharmaceutical law. The Ministry of Health of Ukraine and the National Health Service of Ukraine are responsible for the protection of human rights and freedoms, human life and health, patients, and the nation’s gene pool, as well as privileged categories of citizens. State institutions on the basis of the Constitution of Ukraine, Laws of Ukraine, regulations of Ukraine and Resolutions of the Cabinet of Ministers of Ukraine during the implementation of the "Program of Medical Guarantees" for 2022 decide organizational and legal, medical and pharmaceutical, social and economic issues of the program of state guarantees of medical care population in 2022 according to ICD-11.